Effect of Different Saffron Corm Weights and Planting Distances on Yield and Number of Leaves - Zahirian, Gul Ahmad; said, Masood; Zahiryan, Rohullah (Journal of Natural Sciences – Kabul University, 2020)
The saffron yield per jerib of land was observed in each treatment and replication. In treatments 1, 2, and 3 (with small-sized saffron corms weighing 2-6 grams), the yield was lower, ranging from 6.35 to 25.4 grams. In treatments 4, 5, and 6 (with medium-sized saffron corms weighing 7-10 grams), the yield was moderate, ranging from 273.02 to 323.8 grams. In treatments 7, 8, and 9 (with large-sized saffron corms weighing 11-13 grams), the yield was higher, ranging from 393.65 to 507.94 grams. Treatment 2 produced the lowest average saffron yield (12.7 grams), while treatment 7 produced the highest average yield (480.42 grams). Each treatment showed different saffron yield outcomes.